PEMBOBOLAN REKENING NASABAH BANK RIAU KEPRI - Yola Feby Charita; Gunardi Lie; Moody R. Syailendra (PROSIDING SERINA, 2021)
Banks are an important element in running the economy of a country. Sending, storing, and exchanging money can be done so that banks are important and must exist in a country. In this day and age, technology is very sophisticated, everything can happen, especially crimes committed by irresponsible people. One of the crimes in the banking world is the burglary of a bank customer account in Riau Riau Islands which makes many customers restless. If it is not handled properly, similar crimes will repeat themselves and destroy the trust of bank customers, so the author conducts an analysis for this case. Banking crimes are increasingly being carried out so that the perpetrators must be punished accordingly in order to have a deterrent effect. The purpose of this paper is to analyze banking crimes, increase awareness of banking crimes, and learn more about the Banking Act. In this scientific work, the author uses qualitative methods so that the data generated from the results of observations and community research as well as the information provided to examine more deeply and find the meaning of the case. Based on the results of the analysis, the author can conclude that bank security must be further tightened and improved so that similar crimes do not occur so that customers can calmly store their money in the bank and customers must also increase their awareness of their own accounts to always ensure the amount of balance they have.